Sense and the city : exploring the embodied geographies of urban walking - Middleton, J (Routledge, 2010)
Within UK pedestrian policy, walking is promoted as a sustainable mode of transport that benefits both the body and mind. However, much policy discussion assumes all walking to be the same and a largely self-evident means of transport, whilst many academic engagements with walking are highly abstract theorisations that lack any systematic empirical exploration of actual pedestrian practices. As such, there is little that unpacks the experiences of those who navigate, negotiate and traverse the city streets in their day-to-day lives. In contrast, this paper aims to situate and understand the practice of everyday walking in the unfolding experiences of urban pedestrians. Walking is positioned and understood as a socio-technical assemblage that enables specific attention to be drawn to the embodied, material and technological relations and their significance for engaging with everyday urban movements on foot. The analysis draws upon in-depth interview and walking photo diary data from participants in the inner London boroughs of Islington and Hackney. Particular analytic attention to the different styles and conventions of urban walking and how these are intimately linked to bodily senses and the materiality of the city provides an opportunity for creating an increased engagement between urban and pedestrian policy and urban and social theory.